Laju penurunan kualitas virgin coconut oil (vco) dalam wadah botol kaca bening dengan metode Accelerated Shelf Life Testing (ASLT) - Fitrian, Nurul; Aladin, Andi; Kalsum, Ummu (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Indonesia is a tropical country, has a wealth of coconut trees spread throughout its territory, from Sumatra to Papua. This country is the largest coconut producer in the world and is the main supplier of coconut commodities in the global market. This condition opens up great opportunities to develop coconuts into various useful products. One of the popular coconut products is coconut oil or Virgin Coconut Oil (VCO). The purpose of this study was the effect of VCO storage time in an open glass bottle container at a temperature of 40°C on the quality parameters of peroxide number and turbidity. The results of the study showed an increase in the value of VCO both in peroxide number and Turbidity every week for seven weeks of storage in an open glass bottle container at a temperature of 40°C. Where the shelf life based on the peroxide number is 42 days and for the Turbidity shelf life 46 days. This increase indicates a physical change in VCO due to interaction with environmental conditions such as temperature, light, humidity and oxygen exposure, which affect VCO. The effect of time (t, days) of VCO storage in open glass bottles on the quality parameters of the peroxide number (Bp, meq / Kg) and turbidity (TB, NTU) can be seen in the exponential equation. The equation for Bp = 1.0536. Exp [ 0.0249 . t ], while the equation for Tb = 1.0247. Exp [ 0.0347. t ] . Based on the analysis of the shelf life of VCO, it was found that the peroxide number and turbidity values tend to increase with increasing storage time.